2021
DOI: 10.1002/rse2.224
|View full text |Cite
|
Sign up to set email alerts
|

Airborne laser scanning reveals increased growth and complexity of boreal forest canopies across a network of ungulate exclosures in Norway

Abstract: Large herbivores are often classed as ecosystem engineers, and when they become scarce or overabundant, this can alter ecosystem states and influence climate forcing potentials. This realization has spurred a call to integrate large herbivores in earth system models. However, we lack a good understanding of their net effects on climate forcing, including carbon and energy exchange. A possible solution to this lies in harmonizing data across the myriad of large herbivore exclosure experiments around the world. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The ALS data available to us were at relatively low point densities (≤5 points m 2 ) in contrast to what can be achieved using bespoke collected data (either from airborne or terrestrial‐based LIDAR scanning). However, the available data were clearly at high enough resolution to detect moose impacts on forest canopies, and a previous study has highlighted the similarity between ALS and field data in assessing moose effects on forest canopies (Kolstad et al, 2021; Snøan, 2019). We used externally calibrated models to estimate AGB from ALS metrics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ALS data available to us were at relatively low point densities (≤5 points m 2 ) in contrast to what can be achieved using bespoke collected data (either from airborne or terrestrial‐based LIDAR scanning). However, the available data were clearly at high enough resolution to detect moose impacts on forest canopies, and a previous study has highlighted the similarity between ALS and field data in assessing moose effects on forest canopies (Kolstad et al, 2021; Snøan, 2019). We used externally calibrated models to estimate AGB from ALS metrics.…”
Section: Discussionmentioning
confidence: 99%
“…AGB was predicted for each plot using equations specific to the location, forest type and stand age of the site. For all Fennoscandian sites, the equation for AGB1999 from (Økseter et al, 2015) was used (accounting for the correction to a typographical error as reported by Kolstad et al (2021)). For the sites in Canada and the USA, equations from Boudreau et al (2008) were used, depending on forest type.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data set also included detailed measurements of diameter‐at‐ground‐level (mm) and height (cm) for trees at Trøndelag sites in 2016. We chose to exclude trees greater than 6 m in height, as these were likely retained at the harvest (Kolstad et al., 2022). We then used allometric biomass models to estimate aboveground tree biomass for each tree in the long‐term data set.…”
Section: Methodsmentioning
confidence: 99%